Le Falstaff de Manfredo Maggioni et Michael Balfe : façonner un opéra italien pour le public anglais - Céline Frigau (Revue LISA)
Based on Shakespeare’s Merry Wives of Windsor, Michael Balfe’s Falstaff, created in 1838 for London’s Italian opera audiences, was the work of an Italian librettist, Manfredo Maggioni, and an Irish composer, a first in a theatre where only Italian maestri were commissioned for new works. Balfe’s and Maggioni’s combined efforts resulted in a truly genuine Italian opera buffa. Not only is it sung in Italian but it also respects the structural codes, vocal and scenic practices which make it recognizable as an opera buffa on the aesthetic stage of the time, and above all on the English stage. The issue of rewriting implies here a reflection on the intimately linked processes of production and reception. Through the study of the libretto and score, its contextualization, as well as contemporary accounts, we will be concerned both with questioning the expectations of Falstaff’s London public and with circumscribing the frontiers of an aesthetic category named “Italian opera”. The term defines itself far from the Italian peninsula at the moment when it comes into contact with non Italian-speaking spectators. As a result of cultural exchanges on the European scale, Falstaff aims both at pleasing Her Majesty’s Theatre’s audiences and, if possible, at gaining international fame as an authentic opera buffa. Yet the opera only obtained a “succès d’estime”, and was never performed again. It nevertheless represents an essential step not only in the works of its composer but in the history of opera in England itself.